Analysis of wild ungulate‐livestock interface in Europe: preliminary results. Issue 12 (10th December 2021) - ,; Illanas, S; Acevedo, P; Apollonio, M; Blanco‐Aguiar, JA; Brivio, F; Croft, S; Cretois, B; Fernández‐López, J; Ferroglio, E; Keuling, O; Linnell, JDC; et al.
Abstract: The ENETWILD consortium (www.enetwild.com ) aims at progressively defining the spatial interface between wild ungulates and livestock in Europe, which is essential to evaluate the risk for shared diseases. This is to provide preliminary risk maps of possible wild‐domestic interfaces at European scale using relatively similar sized regions by compiling, for the first time, comprehensive data for both groups, wild and domestic ungulates in the continent. We spatially represented (i) the richness of species (livestock and wild ungulates), (ii) their specific occupancy and abundance (the latter for livestock), and finally, (iii) their spatial overlapping over Europe. Species richness in animal communities, including wildlife and domestic hosts, may moderate pathogen transmission and disease outcome.. As a first step, we should characterize the diverse assemblages of animal communities at large scale to better understand possible scenarios for further assessment of shared infection dynamics. About 90% of Europe land area hosts from one to five species of wild native ungulates. Therefore, the interface between livestock and wildlife is wide spread over the European continent. Native wild boar, roe deer and reed deer are widely distributed species, present in most possible assemblages of wild/domestic communities over Europe. The richness of ungulate species is high in Central Europe, from West to East, from the Alps (where the presence of mountain ungulates adds richness), extending to countries with important big game tradition and presence of introduced species, and finally, to Eastern Europe (where also typically northern species such as bisons appear)... To sum, we described by pair of species a wide diversity of potential interfaces, which had variable distribution areas.. While the analysis presented herein is purely spatial and at administrative level, the interface between wild and domestic ungulates is influenced by livestock husbandry (e.g., enclosed, herded or free‐ranging, level of biosecurity), landscape and land uses, and wildlife management practices, among other factors, operating locally. Therefore, there is need for a more detailed picture of the interface at European scale.